PELAYANAN PENANGANAN ANAK BERHUBUNGAN HUKUM (ABH) PADA PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK (P2TP2A) KOTA PEKANBARU - Rians "; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Children are the gift from God Almighty as the next generations. However, in their daily lives, sometimes children will have difficult situations that make them commit unlawful actions that will ultimately make children dealing with the law and then known as ABH. P2TP2A as a government institution must be the first to provide assistance to the ABH to ensure that children's rights are fulfilled. This study aims to determine how the service of handling ABH by P2TP2A Kota Pekanbaru by looking at what factor affect the P2TP2A service. The concept of theory used by service theory according to Mulyadi that refers to Service procedure, time of completion, service costs, service products and competency of officers. In this study using a qualitative method with descriptive data analysis. In data collection researchers used interview techniques, observation and documentation and data analysis with qualitative descriptive methods. Lack of experts, lack of budget, and availability of facilities and infrastructure became the main factors in the service of handling ABH by P2TP2A Kota Pekanbaru.  Keywords: Service, Children, Law